Provable security signcryption scheme based on RLWE without trapdoor - Zhen LIU; Yiliang HAN; Xiaoyuan YANG; Shuguang LIU (Tongxin xuebao)
In view of the existing efficiency and security problems of lattice based signcryption,with the ABB16’s signature scheme ring-TESLA,a signcryption scheme without trapdoor named RLWE-SC was constructed,which achieved indistinguish ability against adaptive chosen cipher text attack (IND-CCA2) security and strongly existential unforgeability against chosen message attack (SUF-CMA) security respectively in terms of confidentiality and authentication based on the problem of learning with errors on ring.The size of the public and private keys was optimized by the construction on the ring.The complex trapdoor generation and preimage sample calculation was avoided by the structure without trapdoor.Efficiency analysis and experiment shows that RLWE-SC has better computational and communication performance than other similar lattice-based signcryption schemes with the same security strength.